Matrix Operators and bv Sequence Spaces - Anwar, Khoirul; Supama (Journal of Research in Mathematics Trends and Technology, 2024)
In this paper, we study about the matrix domain of the sequence space by several triangle infinite matrices, namely the Cesaro mean of order one matrix, the Generalized Weighted matrix, and the Riesz matrix. Several things related to the matrix domain that will be observed include isomorphism of sequence spaces, -spaces, Schauder bases, -duals, -duals, -duals, and also the characterization of a mapping of a sequence space by some classes of matrix transformations. Furthermore, we also discuss inclusion relations of several matrix domains of the sequence space .